Examining the Relationship Between Stock Returns and Investor Sentiments: The Moderating Effect of Weather Patterns - M. Rahila Begam; Manivannan Babu
This study examines the moderating effect of weather patterns on the relationship between stock returns and investor sentiments. Data were collected from 386 investors using a structured questionnaire from Tamil Nadu, India. The findings showed that weather patterns positively impact the association between stock returns and investor sentiments. However, it was shown that the direct effects of stock returns on investor sentiments were found to be not significant. As a result, by enlightening the relationship between stock returns and investor sentiments in the context of the developing world, this research makes a valuable contribution to the literature on investor sentiments. Furthermore, from the finding of the study, the relationship between stock returns needs to consider the constructs such as price volatility and margin trading behaviour.